Phenotypic plasticity in adults of Anticarsia gemmatalis exposed to sub-doses of Bt-based bioinsecticide - Fernandes, F. O. [UNESP]; Souza, T. D. [UNESP]; Sanches, A. C.; Carvalho, I. R.; Dias, N. P.; Desiderio, J. A. [UNESP]; Polanczyk, R. A. [UNESP] (Instituto Internacional de Ecologia, 2022)
Anticarsia gemmatalis Hünber, 1818 is one of the main defoliating species in the soybean crop. Bacillus thuringiensis Berliner, 1915, is a bacterium used in the biological control of this pest species. Resistant populations and their sublethal effects caused by the use of the bacteria have already been reported; however, there are no studies on phenotypic plasticity in adulthood exposed to Bt-based bioinsecticide sub-doses. This study aimed to evaluate the morphometry of A. gemmatalis adults under laboratory conditions submitted to the Bt-based bioinsecticide Dipel® over the three generations. The body segments mensuread were width, length, and area of the anterior and posterior wings, the weight of the integument, chest, abdomen, wings, and the whole adult of males and females. Among the treatments, LC5 in the first generation and LC10 in the second generation were those with lower thresholds in relation to the weight of the chest and abdomen, considering the proportions of the body smaller than the females. The female’s weight adulthood was reduced by 10% about males, and, only in the first generation. Males have larger body size and more pronounced phenotypic plasticity than females. Here, we demonstrate the first study assessing the phenotypic plasticity of A. gemmatalis adults.

Anticarsia gemmatalis Hünber, 1818 é uma das principais espécies desfolhadoras da cultura da soja. Bacillus thuringiensis Berliner, 1915, é uma bactéria utilizada no controle biológico dessa espécie de praga. Populações resistentes e seus efeitos subletais causados pelo uso da bactéria já foram relatados, no entanto, não há estudos sobre a plasticidade fenotípica na idade adulta exposta a subdoses de bioinseticida à base de Bt. Este trabalho teve como objetivo avaliar a morfometria de adultos de A. gemmatalis em condições de laboratório submetidos ao bioinseticida Dipel® ao longo de três gerações. Os segmentos corporais mensuráveis eram largura, comprimento e área das asas anterior e posterior, o peso do tegumento, tórax, abdômen, asas e todo o adulto de machos e fêmeas. Dentre os tratamentos, CL5 na primeira geração e CL10 na segunda geração foram aqueles com limiares mais baixos em relação ao peso do tórax e abdômen, considerando as proporções do corpo menores que as do sexo feminino. O peso da fêmea na idade adulta foi reduzido em 10% em relação aos machos e, apenas na primeira geração. Os machos têm tamanho corporal maior e plasticidade fenotípica mais pronunciada do que as fêmeas. Este estudo demonstra o primeiro estudo avaliando a plasticidade fenotípica de adultos de A. gemmatalis.
Plasticidade fenotípica morfométrica em adultos de Anticarsia gemmatalis Hübner, 1818 expostos a subdoses de Bacillus thuringiensis Berliner, 1911
Keywords: allometry measure; morphometry; velvet bean caterpillar; Bacillus thuringiensis; phenotype; medida de alometria; morfometria; lagarta da soja; Bacillus thuringiensis; fenótipo